Pengaruh Variasi Holding Time pada Proses Pack Carburizing dengan Arang Tempurung Kelapa Barium Carbonat Terhadap Sifat Fisik dan Mekanik Baja ST 42 - mastur; Warso; Satria Jati, Unggul (Accurate: Journal of Mechanical Engineering and Science, 2023)
Iron-based production machine components are chosen to support productivity. Steel is a metal material that is easily found on the market, but it has not fulfilled the desires of consumers in the market. This steel can be hardened by heat treatment (heat treatment). The surface treatment process is carried out to obtain the desired hardness, this can be done by increasing the carbon (C) element in the steel material, the carbon content in the standard steel structure is 0.3% - 0.59% the carbon content will have an effect. on hardness, one way to increase the element carbon (C) in steel and increase the hardness on its surface is by carburizing. This research will examine the hardness level of low carbon steel by using a pack carburizing process with different times of 2; 2.5 and 3 hours and the quenching process with pure water media.. The purpose of this study was to determine the effect of holding time on the pack carburizing process with coconut shell charcoal - barium carbonat on the hardness value of ST 42 steel. Besides that for effect of holding time on the pack carburizing process with coconut shell charcoal on the microstructure. There are differences in the surface hardness and microstructure values ​​ before and after the carburizing process. Where the highest hardness value occurs at a holding time of 3 hours with a hardness value of 872.9 HVN or an increase of 382% of the raw material and is supported by the dominance of the martensite phase which is more and more evenly distributed. Compared to the ST 42 steel raw material before the pack carburizing process was carried out, the hardness value was 174.8 HVN. A dominant microstructure consisting of a ferrite phase and a little bit of pearlite dominance.